2017
DOI: 10.1186/s12889-017-4306-8
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional drowning: Role of medicinal drugs and alcohol

Abstract: BackgroundAlcohol is a well-known risk factor in unintentional drownings. Whereas psychotropic drugs, like alcohol, may cause psychomotor impairment and affect cognition, no detailed studies have focused on their association with drowning. Finland provides extensive post-mortem toxicological data for studies on drowning because of its high medico-legal autopsy rates.MethodsDrowning cases, 2000 through 2009, for which post-mortem toxicological analysis was performed, came from the database of the Toxicological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…For example, some landlocked countries may have more exposure to drowning in inland waterways such as rivers and lakes 41. This study did not explore the circumstances leading to drowning, aquatic location where the incident occurred, or the impact of alcohol, which is a significant contributor to drowning 42–44. There is also further work required to quantify the burden of drowning among migrants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some landlocked countries may have more exposure to drowning in inland waterways such as rivers and lakes 41. This study did not explore the circumstances leading to drowning, aquatic location where the incident occurred, or the impact of alcohol, which is a significant contributor to drowning 42–44. There is also further work required to quantify the burden of drowning among migrants.…”
Section: Discussionmentioning
confidence: 99%
“… 41 This study did not explore the circumstances leading to drowning, aquatic location where the incident occurred, or the impact of alcohol, which is a significant contributor to drowning. 42–44 There is also further work required to quantify the burden of drowning among migrants. Future drowning studies should also encompass all drowning deaths (ie, transport related, disaster related, unintentional, intentional and undetermined intent).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol is a known risk factor for drowning [5], with alcohol known to be present in 26% of Australian river drownings between 2002-2012 [21], 38% of drowning deaths in Sweden between 1992-2009 [22], 65% of boating-related drownings in Finland between 2000-2009 [23], and 37% of drowning deaths in Canada between 2008 and 2012 [24]. This study identified 26% of drowning deaths which were known to involve victims with a BAC ≥0.05, with an increased risk of alcohol-related drowning when compared to non-holidays.…”
Section: Discussionmentioning
confidence: 99%
“…• • More beachgoers in the 16-29 age group consumed alcohol prior to swimming (38%) than the (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) 16% and 50+ (13%) age groups alcohol and 38.3% of participants reported their dive clubs as having a responsible attitude toward alcohol. In summarising these findings, several trends were evident.…”
Section: Understanding Alcohol Use and Aquatic Activitiesmentioning
confidence: 99%